Application of endoscopic retrograde cholangiopancreatography combined with intraductal ultrasonography in differential diagnosis of enign and malignant biliary stricture and nursing management (经内镜逆行性胰胆管造影术联合胆管腔内超声在良恶性胆管狭窄鉴别诊断中的应用及护理) - YANG Min (杨敏); HU Jifen (胡继芬) (Association of Integrative Nursing, 2023)
To explore the application and nursing cooperation of endoscopic retrograde cholangiopancreatography (ERCP) combined with intraductal ultrasonography (IDUS) in differential diagnosis of benign and malignant biliary stricture. From January 2015 to December 2020, 208 patients with biliary stricture of unknown origin were treated with ERCP combined with IDUS. The operation was successfully completed in all 208 cases. The diagnosis was confirmed by biopsy, operation and follow-up. There were 87 cases of malignant stricture, including 50 cases of cholangiocarcinoma (21 cases in the lower segment, 19 cases in the middle segment, 10 cases in the upper segment / hilar), 15 cases of pancreatic cancer, 12 cases of ampullary cancer, 10 cases of other metastatic tumor invasion, and 121 cases of benign stricture. There were 92 cases of hyperamylasemia and 1 case of delayed bleeding, no perforation was reported. After fasting, anti-inflammatory, hemostasis, enzyme inhibition and rehydration, they were all improved and discharged. Psychological guidance and perfect preparation before operation, tacit cooperation during operation, prevention and observation of complications, and careful nursing after operation are key issues to ensure the successful completion of the examination. (探讨经内镜逆行性胰胆管造影术(ERCP)联合胆管腔内超声(IDUS)在良恶性胆管狭窄鉴别诊断中的应用和护理配合。回顾性分析2016年1月-2021年12月医院收治的208例不明原因胆管狭窄行ERCP联合IDUS治疗的患者的临床资料。208例均成功完成操作, 通过活检病理、手术及随访确定诊断, 恶性狭窄87例, 其中胆管癌50例(下段21例、中段19例、上段／肝门部10例), 胰腺癌15例, 壶腹癌12例, 其他转移肿瘤侵犯10例; 良性狭窄121例。术后并发高淀粉酶血症92例, 发热20例, 迟发性出血1例, 无术后穿孔情况。患者给予禁食、抗炎、止血、抑酶、补液治疗后均好转出院。术前做好心理指导和完善的准备, 术中默契配合, 做好并发症的预防和观察, 术后精心护理, 是保障检查顺利完成的重要环节。)